2014
DOI: 10.3402/tellusb.v66.25897
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability of clouds, solar radiation and temperature at a high-latitude coastal site in Norway

Abstract: A B S T R A C TThe observed variability of shortwave (SW) irradiance, clouds and temperature and the potential connections between them is studied for the subarctic site Bergen (60.48N, 5.38E), located on the Norwegian west coast. Focusing on the quality and spatial representativity of the data, we compare observations from independent instruments and neighbouring measurement sites. The observations indicate that the decrease of sunshine duration and SW irradiance during the 1970s and 80s in Bergen is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
5
17
0
Order By: Relevance
“…While it is obvious that clouds are important, the difficulty here is that there are several factors that control their impact. For example there are considerable regional differences in fractional cloudiness (Norris, 2005): fractional cloudiness is constant in northern Europe (Parding et al, 2014) and in Germany before 1997 , well after the minimum in global radiation in 1984, and has declined in the period after 1997 in Switzerland and Germany, at least until 2010 (Ruckstuhl et al, 2010). Furthermore, cloud optical thickness changes can be the result of changes in microphysics or cloud thickness and current observations are not able to separate the two effects.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…While it is obvious that clouds are important, the difficulty here is that there are several factors that control their impact. For example there are considerable regional differences in fractional cloudiness (Norris, 2005): fractional cloudiness is constant in northern Europe (Parding et al, 2014) and in Germany before 1997 , well after the minimum in global radiation in 1984, and has declined in the period after 1997 in Switzerland and Germany, at least until 2010 (Ruckstuhl et al, 2010). Furthermore, cloud optical thickness changes can be the result of changes in microphysics or cloud thickness and current observations are not able to separate the two effects.…”
Section: Introductionmentioning
confidence: 94%
“…In the context of Europe there have been a considerable number of regional studies that focus on trends in global radiation and their attribution, such as in Germany (Liepert and Tegen, 2002;Liepert and Kukla, 1997;, in Germany and Switzerland combined (Ruckstuhl et al, 2008;Ruckstuhl and Norris, 2009;Ruckstuhl et al, 2010), in Estonia (Russak, 2009), in the general Baltic states (Ohvril et al, 2009), in Spain (Mateos et al, 2014), in Norway (Parding et al, 2014), northern Europe in general (Stjern et al, 2009) and in Italy (Manara et al, 2015). Even though there are regional differences, the summarized global or allsky radiation data from Europe combined display a minimum in [1984][1985] at the end of a "dimming" period with a subsequent return to higher values.…”
Section: Introductionmentioning
confidence: 99%
“…The particular case of causes behind (in situ) SSR trends in Northern Europe has been investigated by Stjern et al [47] and Parding et al [48]. They found that cloudiness decrease appears to be the main driver for the 1990s-2000s brightening in Scandinavia, with likely additional contributions from decreasing aerosol concentrations.…”
Section: Assessment Of Ssr Trendsmentioning
confidence: 99%
“…Changes in the transparency of the atmosphere due to variations in anthropogenic aerosol emissions and/or cloudiness are considered as the major factors explaining this dimming/brightening phenomenon [ Stanhill and Cohen , ; Long et al ., ; Ohmura , ; Wild , ; Gan et al ., ; Parding et al ., ; Cherian et al ., ; Mateos et al ., ; Wang et al ., ]. However, analysis of the SSR series still poses some challenges that are necessary to overcome in order to better understand their trends during the last decades.…”
Section: Introductionmentioning
confidence: 98%